Poster ideas and bulletin board techniques for libraries and schools - Coplan, Kate. (New York : Oceana Publications, 1981)
Presents many ideas for posters and other visual displays in libraries.
Includes index.
Bibliography: p. 241.
Keywords: Bulletin boards; Handicraft; Posters in education; Bulletin boards; Handicraft; Posters in education